Dinamika Ilmu Pengetahuan Dunia dalam Konteks Sistem Ekonomi Konvensional dan Sistem Ekonomi Islam - Sugiyanti, Melisa; Akbar, Ilham Muhammad; Febyana, Nadia Noor; Aprilia, Dwita (Sharia Economics Study Program Faculty of Islamic Economics and Business UIN Sunan Gunun, 2024)
This research explores the dynamics of world science in the context of conventional economic systems and Islamic economic systems. The background reveals the central role of science in stimulating economic growth, as stated by Joseph E. Stiglitz, while the Islamic economic system emphasizes the integration of science with Islamic ethical values, as stated by Timur Kuran. The aim of the research is to investigate the contribution of science to economic growth in both paradigms, highlighting the essential comparison and potential integration of Islamic ethical values. The research method uses a comparative approach with literature analysis and in-depth interviews with economic experts and practitioners of Islamic economics. The results of the analysis show that science plays a role in the development of conventional economic systems and Islamic economic systems and encourages innovation and growth. This is demonstrated by the Islamic economic system which combines science with Islamic ethics, offering an inclusive and sustainable model. This comparison illustrates differences in views and the potential for integration, where Islamic ethical values can guide the application of science to achieve balanced economic growth. The implication of this research is the need to increase public education and awareness, government support, and the integration of ethical values in economic policy to achieve sustainable and inclusive economic growth.